A Randomized Non‐overlapping Encryption Scheme for Enhanced Image Security in Internet of Things (IoT) Applications - Muhammad Aqeel; Arfan Jaffar; Muhammad Faheem; Muhammad Waqar Ashraf; Nadeem Iqbal; Shahid Yousaf; Hossam Diab (Engineering Reports)
ABSTRACT The rapid proliferation of Internet of Things (IoT) devices has underscored the critical need to safeguard the data they store and transmit. Among various data types, digital images often carry highly sensitive information, making their protection against breaches essential. This study introduces a novel image encryption algorithm specifically designed to bolster the security of images in resource‐constrained IoT ecosystems. Leveraging the randomness of a 5D multi‐wing hyperchaotic map, the proposed method employs pairs of non‐overlapping rectangles to induce confusion by swapping the pixels they encompass. Repeated iterations of this operation achieve significant confusion effects, enhancing encryption strength. To validate the robustness of the proposed algorithm, standard benchmark images were utilized, and rigorous security metrics —including information entropy, correlation coefficient, histogram uniformity, and resistance to differential attacks —were analyzed. Results demonstrate that the algorithm not only ensures strong protection against unauthorized access but also maintains low computational complexity, making it ideal for IoT applications. This research provides a foundational step toward ensuring the confidentiality and integrity of visual data in an increasingly interconnected digital world.